Neuroanatomy of dyslexia: An allometric approach. (16th February 2020) - Peyre, Hugo; Mohanpuria, Neha; Jednoróg, Katarzyna; Heim, Stefan; Grande, Marion; van Ermingen‐Marbach, Muna; Altarelli, Irene; Monzalvo, Karla; Williams, Camille Michèle; Germanaud, David; Toro, Roberto; Ramus, Franck
Abstract: Despite evidence for a difference in total brain volume between dyslexic and good readers, no previous neuroimaging study examined differences in allometric scaling ( i.e. differences in the relationship between regional and total brain volumes) between dyslexic and good readers. The present study aims to fill this gap by testing differences in allometric scaling and regional brain volume differences in dyslexic and good readers. Object‐based morphometry analysis was used to determine grey and white matter volumes of the four lobes, the cerebellum and limbic structures in 130 dyslexic and 106 good readers aged 8–14 years. Data were collected across three countries (France, Poland and Germany). Three methodological approaches were used as follows: principal component analysis (PCA), linear regression and multiple‐group confirmatory factor analysis (MGCFA). Difference in total brain volume between good and dyslexic readers was Cohen's d = 0.39. We found no difference in allometric scaling, nor in regional brain volume between dyslexic and good readers. Results of our three methodological approaches (PCA, linear regression and MGCFA) were consistent. This study provides evidence for total brain volume differences between dyslexic and control children, but no evidence for differences in the volumes of the four lobes, the cerebellum or limbic structures, once allometry is taken into account. It also finds no evidence for a difference in allometric relationships between the groups. We highlight the methodological interest of the MGCFA approach to investigate such research issues. Abstract : This study is the first to examine differences in allometric scaling in dyslexia. We replicated the well‐established finding of a difference in total brain volume between dyslexic and good readers. The present study did not find any differences in allometric scaling or lobar brain volume differences between dyslexic and good readers.